INNOVATION OF PROCESSED FOOD PRODUCTS FROM CULTIVATION IN A BUCKET - Wahana, Siti (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
The aims of this activity are to optimize the local potential of catfish as an alternative processed food and educate the community in Desa Wiyong to produce the food with natural ingridients. This activity was carried out in Blok 4 Desa Wiyong Cirebon in December until March 2021. The methods used were a Focus Group Discussion, counseling, training and assistance, demonstration, and evaluation and monitoring. The results of this activity show that most people are eager to produce the catfish into some processed foods such as bakso lele and cilok lele with good taste and market quality.